(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Hypertension is a leading contributor to global burden of cardiovascular as well as cerebrovascular mortality and morbidity. This paper presents a study on prescription patterns of antihypertensive drugs at medicine ward of a private hospital. An observational study was done for 6 months period (1st March 2015 to 30th August 2015) on 82 Patients at Medicine ward of Southern Medical College Hospital. The objectives of this study were to identify whether monotherapy or combination therapy was most effective in controlling blood pressure, to identify types of antihypertensive drugs most commonly prescribed, to find out most preferred combinations and to see if prescription pattern complied with existing guidelines.Patients of 18 years old or above diagnosed as hypertensive according to JNC-7 and those being prescribed with antihypertensives as well as given consent for the study were included. Among 82 hypertensive patients, male constituted 53.7% and female 46.3%. Monotherapy was prescribed for 42.7% and combination therapy for 57.3% patients. 42.7% received two drugs, 13.4% received three drugs and 1.2% received four drug combinations. Of all monotherapy users, Angiotensin Receptor Blocker (ARB) was most prescibed, used in 77.2% cases. Regarding combination therapy, most preferred combination was ARB and calciumchannel- blocker, used in 44.6% cases. Olmesartan (79.4%) was most preferred as ARB. Combination therapy was more preferred than monotherapy and two drug combination was mostly selected. Angiotensin Receptor Blocker was mostly used agent. Existing guidelines had implications in prescribing pattern of antihypertensive drugs. JCMCTA 2016 ; 27 (2) : 39- 43